2011
DOI: 10.1167/iovs.10-5441
|View full text |Cite
|
Sign up to set email alerts
|

Cycloplegic and Noncycloplegic Refractions of Chinese Neonatal Infants

Abstract: The level of hyperopia was very high in these infants, and the offsetting tonic accommodation demonstrated by the difference between CSE and nCSE was much higher than in any previous report. Low amounts of infantile hyperopia and high astigmatism are associated with future myopia in the West. The Chinese neonates in this study had high amounts of hyperopia and little astigmatism, yet they are at high risk to become myopic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 20 publications
3
26
0
2
Order By: Relevance
“…Overall, this comparison suggests that refractive development in Chinese children over this age range is very similar to that seen in children of European origin, with little myopia detected until children reach the age of 5–6, provided that cycloplegia is adequate. Other results suggest that neonatal refractive development in Chinese children may also be similar to that in children of European origin [29], [32]. After the age of 5–6, possibly due to the impact of high amounts of study and limited time outdoors [33][35], the prevalence of myopia increases markedly in some East Asian populations to produce the current myopia epidemic [36][38].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Overall, this comparison suggests that refractive development in Chinese children over this age range is very similar to that seen in children of European origin, with little myopia detected until children reach the age of 5–6, provided that cycloplegia is adequate. Other results suggest that neonatal refractive development in Chinese children may also be similar to that in children of European origin [29], [32]. After the age of 5–6, possibly due to the impact of high amounts of study and limited time outdoors [33][35], the prevalence of myopia increases markedly in some East Asian populations to produce the current myopia epidemic [36][38].…”
Section: Discussionmentioning
confidence: 93%
“…We have not studied children under the age of 3, and there are few studies on such children of Chinese origin. However, Thorn and colleagues [29] have examined Chinese neonates, finding that the mean SE was +3.55 D, while the mean SE without cycloplegia was +0.58 D. The major difference between cycloplegic and non-cycloplegic refraction illustrates the importance of adequate cycloplegia in young children. The results of Thorn and colleagues suggest that Chinese neonates are highly hyperopic, as are neonates of European origin [30], [31].…”
Section: Discussionmentioning
confidence: 99%
“…[11, 12] There are also some data suggesting that differences in cycloplegic and non-cycloplegic refraction can occur in older age ranges thus affecting the population prevalence estimates of different refractive errors. [13] Our study confirmed the findings from previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…At birth, refractive state, measured with cycloplegia, is broadly distributed, ranging from low myopia (−1 to −4 D) to high hyperopia (up to 8 D) with a mean refraction of low (2 D) to moderate (3.5 D) hyperopia (Chen et al, 2011; Cook and Glasscock, 1951). This may reflect genetic factors that determine the location of the focal plane (corneal and lens curvatures and spacing) and the axial length before there is guidance from the emmetropization mechanism (Siegwart, Jr. and Norton, 2011).…”
Section: Human Studiesmentioning
confidence: 99%